Soaring 21st century mathematics: Business math - Flores, Quennie S. (Animo Repository, 2016)
This concept-based, learner-centered book is intended for senior high school students pursuing careers in banking and finance, management, marketing, hotel and restaurant management, tourism, and other business courses with mathematical concepts relevant to a business curriculum.